Plexus anesthesia versus general anesthesia for carotid endarterectomy: A systematic review with meta-analyses. (May 2021) - Marsman, M.S.; Wetterslev, J.; Keus, F.; van Aalst, D.; van Rooij, F.G.; Heyligers, J.M.M.; Moll, F.L.; Jahrome, A.Kh.; Vriens, P.W.H.E.; Koning, G.G.
Abstract: Introduction: Traditional carotid endarterectomy is considered to be the standard technique for prevention of a new stroke in patients with a symptomatic carotid stenosis. Use of plexus anesthesia or general anesthesia in traditional carotid endarterectomy is, to date, not unequivocally proven to be superior to one other. A systematic review was needed for evaluation of benefits and harms to determine which technique, plexus anesthesia or general anesthesia is more effective for traditional carotid endarterectomy in patients with symptomatic carotid stenosis. Methods: The review was conducted according to our protocol following the recommendations of Cochrane and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Searches were updated on the October 1, 2020. We did not find any randomized clinical trial comparing plexus anesthesia and general anesthesia in carotid endarterectomy with patch angioplasty matching our protocol criteria in patients with a symptomatic and significant (≥50%) carotid stenosis. Conclusions: Based on the current, high risk of bias evidence, we concluded there is a need for new randomized clinical trials with overall low risk of bias comparing plexus anesthesia with general anesthesia in carotid endarterectomy with patch closure of the arterial wall in patients with a symptomatic and significant (≥50%) stenosis of the internal carotid artery. Protocol unique identification number (UIN): CRD42019139913, (https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=139913 ); Highlights: No conclusive evidence in plexus versus general anesthesia in carotid endarterectomy. We recommend one or more randomized clinical trials on this subject forfilling CONSORT statements. Individual patient datasharing is important to increase sample sizes for future reviews.